Der biblische Kanon: Geschichte und Theologie - Söding, Thomas (Zeitschrift für katholische Theologie, 2006)
The often assumend dichotomy between historical-critical and canonical exegesis can be bridged by the biblical concept of revelation. The canon of OT and NT does not obscure the traces of its development but integrates them into salvation history. Proper understanding of either the canon as revelatory or its development as historical are incomplete one without the other.